Environment-friendly electrolytic manganese residue-based high-strength ceramsite and preparation method thereof

By using electrolytic manganese slag, bentonite and sawdust to prepare ceratops, the problems of low dosage, low strength and non-compliance with environmental protection standards in the prior art are solved, and high-strength, low water absorption and environmentally friendly ceratops are achieved.

CN119775043APending Publication Date: 2025-04-08XIANGTAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037721.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-07
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing electrolytic manganese slag preparation and sintered ceramics have problems such as low electrolytic manganese slag dosage, low strength, high calcination temperature and not meeting environmental protection standards, resulting in low economic benefits.

Method used

Electrolytic manganese slag, bentonite and sawdust are used as raw materials to prepare ceramic granules through drying, crushing, mixing, granulation, drying, roasting and other processes. Bentonite is used to adjust the silicon-aluminum composition and provide flux, reduce the baking temperature and increase the strength of ceramic granules.

Benefits of technology

The prepared ceramic ceram cylinder has a pressure strength of 14~18MPa, a bulk density of less than 1000kg/cm3, and a water absorption rate of less than 10% in 1 hour. It meets the standards for high-strength light and coarse aggregates, and meets the environmental protection standards of the "Technical Specifications for the Control of Manganese Slag Pollution".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775043A_ABST
    Figure CN119775043A_ABST
Patent Text Reader

Abstract

The invention discloses environment-friendly electrolytic manganese residue-based high-strength ceramsite and a preparation method thereof, and belongs to the technical field of solid waste resource utilization. The preparation method comprises the following steps: drying, crushing and uniformly mixing raw materials consisting of electrolytic manganese residues, bentonite and saw dust, adding water, mixing and granulating to obtain granules; the ceramsite has excellent mechanical properties, the cylinder compressive strength of the ceramsite can reach 14-18 MPa, the stacking density of the ceramsite is smaller than 1000 kg / cm < 3 >, the 1h water absorption rate of the ceramsite is lower than 10%, and the ceramsite meets the high-strength light coarse aggregate standard in Lightweight Aggregate and Test Method Part 1: Lightweight Aggregate GB / T 17431.1-2010; and the content of the leached heavy metals, the ammonia nitrogen concentration and the pH value of the ceramsite meet the environmental protection standard requirements in Technical Specification for Control of Manganese Slag Pollution (HJ1241-2022).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an environmentally friendly high-strength ceramsite and a preparation method thereof, in particular to a method for preparing the environmentally friendly high-strength ceramsite by using electrolytic manganese slag, and belongs to the technical field of solid waste resource utilization. Background Art

[0002] Electrolytic manganese is widely used in metallurgy, chemical industry, new energy and other fields. Since most of the domestic manganese ores are poor ores, there are few rich ores, and the composition of manganese ore is very complex, with high phosphorus and high silicon, it is difficult to prepare electrolytic manganese metal, so the production cost is also high.

[0003] At present, with the development of the electrolytic manganese industry, the output of electrolytic manganese slag has further increased, and the pollution is serious. The main hazards brought by electrolytic manganese slag to the environment include occupying a large amount of land, polluting water bodies, and destroying the ecological environment. Therefore, the harmless treatment and resource utilization of electrolytic manganese slag have become urgent problems to be solved. However, the products produced by the resource utilization of electrolytic manganese slag should not only meet the requirements of relevant product standards, but also need to meet the requirements of the "Technical Specifications for Manganese Slag Pollution Control" (HJ1241-2022).

[0004] The literature (“Experimental Study on the Production of Ceramic Aggregates from Electrolytic Manganese Slag” by Huang Chuan et al., Nonmetallic Minerals, September 2013, Vol. 36, No. 5) disclosed that ceramic aggregates were fired with electrolytic manganese slag, fly ash and sawdust as raw materials. The bulk density of the ceramic aggregates obtained according to the optimal experimental scheme was 684 kg / m 3 , water absorption rate of 8.5%, cylinder pressure strength of 4.0 MPa, meet the technical requirements of ordinary lightweight aggregate 700 grade specified in GB / T 17431-2010, the heavy metal content of electrolytic manganese slag ceramsite is lower than the limit value of hazardous characteristic index of GB / T 5085.3-2007, and it is environmentally safe. However, the content of electrolytic manganese slag in the ceramsite is only 42%, the cylinder pressure strength is low, the roasting temperature is high, and the leaching concentration of Mn and ammonia nitrogen in the ceramsite is not tested. The literature ("Roasting mechanism of lightweight low-aluminum–silicon ceramisite derived from municipal solid waste incineration fly ash and electrolytic manganese residue." Xinyuan, et al. Waste Management 2022,153: 264-274) uses waste incineration fly ash and manganese slag as raw materials to co-sinter ceramsite, and the compressive strength of the ceramsite is 5.93MPa and the apparent density is 1.52g / cm 3, meeting the requirements of commercial lightweight aggregate and GB 36600-2018 Class I development land. However, the content of electrolytic manganese slag in the ceramsite is only 35%, and a roasting temperature of 1160°C is required. The literature ("Research on the Mechanism of the Influence of Co-sintering Temperature of Electrolytic Manganese Slag Ceramsite" Ye Dongdong et al., Materials Guide, 2022, Vol. 36, No. 11) uses electrolytic manganese slag, fly ash, and perlite as raw materials to prepare ceramsite. The results show that sintered ceramsite realizes the solidification of Mn by forming manganese calcium pyroxene, and the Mn solidification rate in ceramsite is 99.92%, and it is non-radioactive. However, the content of electrolytic manganese slag in the ceramsite is less than 50%, the water absorption rate is high in 1h, and the roasting temperature needs to reach above 1150°C.

[0005] In summary, there are still some problems in the preparation of sintered ceramsite from existing electrolytic manganese slag. Although ceramsite uses electrolytic manganese slag as raw material, the dosage of electrolytic manganese slag is not high, and it cannot absorb electrolytic manganese slag in large capacity; and the existing electrolytic manganese slag ceramsite has low strength, high required roasting temperature, and whether it meets the environmental protection standards for the resource utilization of manganese slag, etc., which leads to low economic benefits of electrolytic manganese slag ceramsite. Summary of the invention

[0006] In view of the problems existing in the prior art, the first object of the present invention is to provide an environmentally friendly electrolytic manganese slag-based high-strength ceramsite, which has excellent mechanical properties, a cylinder pressure strength of 14-18 MPa, and a bulk density of less than 1000 kg / cm 3 The 1h water absorption rate is less than 10%, which meets the high-strength light coarse aggregate standard in GB / T 17431.1-2010 "Light Aggregate and Its Test Methods Part 1: Light Aggregate". At the same time, the leached heavy metal content, ammonia nitrogen concentration and pH value of the expanded clay meet the environmental protection standards in the "Technical Specifications for Manganese Slag Pollution Control" (HJ1241-2022).

[0007] The second object of the present invention is to provide an environmentally friendly method for preparing electrolytic manganese slag-based high-strength ceramsite. The preparation method uses electrolytic manganese slag as the main raw material and only needs to add a very small amount of bentonite as a regulator, which greatly improves the absorption capacity of the electrolytic manganese slag and reduces the cost of raw materials. The ceramsite sintering can be completed at a relatively low temperature, reducing energy consumption. The prepared ceramsite meets the relevant standards in GB / T 17431.1-2010 "Light Aggregate and Its Test Methods Part 1: Light Aggregate" and "Technical Specifications for Manganese Slag Pollution Control" (HJ1241-2022). The method has a simple process and low cost, and realizes the resource processing of solid waste materials.

[0008] In order to achieve the above technical purpose, the present invention provides an environmentally friendly method for preparing electrolytic manganese slag-based high-strength ceramsite, which comprises drying, crushing and mixing raw materials consisting of electrolytic manganese slag, bentonite and sawdust, adding water for mixing and granulating to obtain pellets; the pellets are dried, roasted and cooled to obtain the pellets.

[0009] The key to the preparation process of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention is to make full use of the components contained in the electrolytic manganese slag itself and the adjustment effect of a small amount of bentonite on the silicon and aluminum components, realize the mineral phase reconstruction in the electrolytic manganese slag at high temperature, form a high-strength ceramic phase, obtain ceramsite with high mechanical strength, and remove ammonia nitrogen by high-temperature volatilization, stabilize heavy metals by wrapping and lattice embedding, and convert alkaline metal oxides into stable minerals, so as to achieve the purpose of "detoxification" of the electrolytic manganese slag and meet the latest technical specifications for manganese slag pollution control. The electrolytic manganese slag is used as the main raw material, and its chemical composition mainly includes SiO2, Al2O3, CaO, MgO, Fe2O3, and K2O, wherein SiO2 and Al2O3 form the main components of the ceramsite skeleton, and in addition, Fe2O3, MgO, K2O and Na2O can act as flux, which can reduce the entire sintering temperature, and at the same time produce a liquid phase to play a filling and wrapping role. Bentonite and sawdust are used as improved components. Bentonite plays a bonding role on the one hand, improving the consolidation strength of ceramsite, and on the other hand, it can adjust the silicon and aluminum components in the ceramsite raw materials. At the same time, bentonite also contains alkaline metal oxides, which can provide more flux components, so that more liquid phase can be produced during high-temperature sintering, so that the ceramic skeleton is filled and wrapped by the liquid phase, and the bonding force between the skeletons is enhanced. Sawdust plays a pore-forming role, increasing the internal porosity of ceramsite and reducing the bulk density of ceramsite. The ceramsite prepared by electrolytic manganese slag and bentonite has excellent mechanical properties, a bulk density of 900, and low water absorption.

[0010] As a preferred solution, the electrolytic manganese slag and the bentonite are composed according to the following mass percentages: 80% to 95% electrolytic manganese slag and 5% to 20% bentonite; the mass of the sawdust is 4% to 8% of the total mass of the electrolytic manganese slag and the bentonite. The present invention aims to consume the electrolytic manganese slag to the greatest extent in the process of preparing ceramsite. However, due to the large loss on ignition of the electrolytic manganese slag, as the proportion of the electrolytic manganese slag is too high, the higher the sintering temperature required in the ceramsite sintering and forming process, the greater the bulk density of the formed ceramsite, which cannot meet the requirements of light aggregate. The key to the present invention is the introduction of bentonite to prepare ceramsite in combination with the electrolytic manganese slag. The introduction of an appropriate amount of bentonite can not only adjust the SiO in the raw materials, but also adjust the amount of bentonite in the raw materials. 2、Al2O3 silicon-aluminum components are used to obtain more ceramic phases with higher mechanical strength. At the same time, bentonite also provides more flux components, which can not only reduce the sintering temperature, but also promote SiO2 and Al2O3 to form more liquid phases. After a series of complex chemical and physical reactions, a stable crystal structure is formed, which becomes the structural basis of the supporting skeleton of ceramsite. The electrolytic manganese slag and the bentonite are further preferably composed of the following mass percentages: electrolytic manganese slag 90-95%, bentonite 5%-10%. Sawdust can be used as a pore-forming agent to increase the internal pores of ceramsite, thereby reducing the bulk density of ceramsite.

[0011] As a preferred solution, the main components and mass contents of the electrolytic manganese slag are: SiO2 37.52-46.22%, Al2O3 10.09-15.06%, CaO 6.03-10.2%, Fe2O3 5.79-7.03%, MnO 2.54-3.61%, MgO 1.82-2.68%. The electrolytic manganese slag raw material of the present invention is the waste slag separated from manganese ore by sulfuric acid leaching, and the total mass content of silicon and aluminum components reaches about 50%, and it is easy to fine-tune the silicon and aluminum components through bentonite to achieve the best silicon-aluminum ratio. Due to the influence of the composition of the ore raw material, the smelting process and technical control, there are differences in the content of silicon, calcium, aluminum, iron and manganese components in different electrolytic manganese slags. Selecting a suitable electrolytic manganese slag is relatively important for preparing ceramsite with excellent performance.

[0012] As a preferred solution, the raw material is crushed to a particle size of 60-80 mesh. The crushing of the present invention adopts a universal crushing method, and the conditions for the universal crushing are: a rotation speed of 20000-25000 r / min and a time of 0.5-1 min.

[0013] As a preferred solution, the mass ratio of the raw material to water is 100:25~30.

[0014] As a preferred solution, the drying conditions are: temperature of 100-105° C. and time of 4-5 hours.

[0015] As a preferred solution, the calcination process is: preheating at 350-550°C for 10-30 minutes at a heating rate of 3-8°C / min, then heating to 1030-1070°C and sintering for 5-20 minutes. Preheating at 350-550°C can not only discharge the physical water and part of the chemically bound water in the pellets, but also decompose part of the organic matter and carbonate in the pellets, creating conditions for the liquefaction of the minerals in the pellets. A further preferred sintering temperature is 1050-1060°C. If the sintering temperature is too low, the ceramsite will not produce enough liquid phase, so that the internal structure of the ceramsite is loose and unstable, so the ceramsite has low strength and high water absorption; and if the sintering temperature is too high, the ceramsite liquid phase will continue to be produced and melted, resulting in the destruction of the ceramsite structure or even adhesion.

[0016] The present invention also provides an environmentally friendly electrolytic manganese slag-based high-strength ceramsite, which is obtained by the preparation method. The environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention has a cylinder pressure strength of 14-18 MPa and a bulk density of less than 1000 kg / cm 3 The 1h water absorption rate is less than 10%, which meets the high-strength light coarse aggregate standard in GB / T 17431.1-2010 "Light aggregate and its test method Part 1: Light aggregate"; and the leached heavy metal content, ammonia nitrogen concentration and pH value of the expanded clay meet the environmental protection standards in the "Technical Specifications for Manganese Slag Pollution Control" (HJ1241-2022).

[0017] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows: 1) In the preparation process of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention, the proportion of electrolytic manganese slag raw materials can reach up to 95%, which realizes the large-capacity consumption of electrolytic manganese slag and realizes resource utilization. The bentonite as an added component is derived from natural minerals, and the added proportion is small, the raw material source is wide, and the cost is low.

[0018] 2) In the preparation process of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention, the mineral components contained in the electrolytic manganese slag itself are utilized. Under the regulation of a small amount of bentonite, the synergistic effect of various raw materials at high temperature produces mineral reconstruction. The obtained ceramsite has excellent mechanical properties, and the cylinder pressure strength can reach 14~18MPa.

[0019] 3) In the preparation process of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention, quartz, gypsum, and mica in the electrolytic manganese slag can be converted into minerals such as calcium feldspar, quartz, and feldspar through solid phase sintering, thereby improving the strength of the ceramsite. At the same time, harmful elements such as manganese are embedded in the ferrite lattice, thereby realizing the harmless treatment of the electrolytic manganese slag. Therefore, the harmful substance content of the ceramsite meets the environmental protection standard requirements in the "Technical Specifications for Manganese Slag Pollution Control" (HJ1241-2022).

[0020] 4) The preparation process of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention is simple, low-cost, low-energy consumption, and meets the requirements of industrial production.

[0021] 5) The cylinder pressure strength of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention can reach 14-18MPa, and the bulk density is less than 1000kg / cm 3 The 1h water absorption rate is less than 10%, which meets the high-strength light coarse aggregate standard in GB / T 17431.1-2010 "Light aggregate and its test methods Part 1: Light aggregate". BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process flow chart for preparing environmentally friendly electrolytic manganese slag-based high-strength ceramsite.

[0023] Figure 2 This is a physical picture of environmentally friendly electrolytic manganese slag-based high-strength ceramsite.

[0024] Figure 3 This is the X-ray diffraction pattern of environmentally friendly electrolytic manganese slag-based high-strength ceramsite. DETAILED DESCRIPTION

[0025] In order for those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the following embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.

[0026] Example 1 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 4%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0027] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mixing and sieving electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ and dry them for 4h. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0028] Example 2 Different from Example 1, the mass percentages of the raw material components in this example are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 6%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0029] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mixing and sieving electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ and dry them for 4h. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0030] Example 3 Different from Example 1, the mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 6%; water accounts for 30% of the total mass of the raw materials, and the preheating temperature is 400° C. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0031] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mixing and sieving electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ and dry them for 4h. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 400°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0032] Example 4 Different from Example 1, the mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 6%; water accounts for 30% of the total mass of the raw materials, and the roasting time is 15 minutes. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0033] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mixing and sieving electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ and dry them for 4h. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 400°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 15 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0034] Example 5 Different from Example 1, the mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 6%; water accounts for 30% of the total mass of the raw materials, and the roasting temperature is 1060° C. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0035] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mixing and sieving electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ and dry them for 4h. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 400°C, preheating time of 30 min, roasting temperature of 1060°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0036] The bulk density, apparent density, 1h water absorption rate and cylinder compressive strength of the electrolytic manganese slag sintered ceramsite prepared in Examples 1 to 7 were tested using the reference standard GB / T 17431.2 2010 "Lightweight aggregate and its test methods Part 2: Lightweight aggregate test methods". The results are shown in Table 2.

[0037]

[0038] It can be seen from the data in Table 2 that the bulk density of the environmentally friendly electrolytic manganese slag-based high-strength ceramsite of the present invention is less than 1000kg / cm 3 The cylinder pressure strength is greater than 6.5MPa, and the 1h water absorption rate is less than 10%, which meets the high-strength light coarse aggregate standard in GB / T 17431.1-2010 "Light aggregate and its test methods Part 1: Light aggregate".

[0039]

[0040] Where - means not detected. From the results in Table 3, it can be seen that the leaching content of harmful substances in environmentally friendly electrolytic manganese slag-based high-strength ceramsite is lower than the standard concentration limit in the "Technical Specifications for Manganese Slag Pollution Control" (HJ 1241-2022). During the sintering process of ceramsite, heavy metals participate in calcium feldspar and cultured feldspar, and exchange ions with Ca to balance charges to form corresponding hybrid minerals, and at the same time participate in the amorphous [Si2O7 6- ], which reduces the heavy metal content in ceramsite. + -N exists in the electrolytic manganese slag mainly in the form of (NH4)2SO4·H2O. During the sintering process of ceramsite, as the temperature rises, the chemically bound water in (NH4)2SO4·H2O is removed to form (NH4)2SO4. When the temperature is higher than 400 ℃, (NH4)2SO4 decomposes and NH4 + -N escapes in the form of NH3 and N2, thus reducing the NH4 in the ceramsite + -N content.

[0041] X-ray diffraction analysis: The X-ray diffraction pattern of the high-strength ceramsite obtained in Example 3 is as follows Figure 3 As shown (the diffraction scanning range is 5~90°), it can be seen that the main phases of expanded clay are quartz (SiO2), calcium feldspar (CaAl2Si2O8), and calcite ((Ca,Na)(Al,Si)2Si2O8), etc. These substances have stable chemical compositions and can effectively enhance the strength of expanded clay.

[0042] Comparative Example 1 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 100%, bentonite 0%, sawdust 6%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, MgO 2.10%.

[0043] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105°C, take out the electrolytic manganese slag, pour it into a crusher and crush it through a 60-mesh sieve; the sawdust is directly sieved through a 60-mesh sieve; b. Manually mix and sieve electrolytic manganese slag, sawdust and water to obtain a mixed raw material in parts by weight; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0044] Example 6 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 90%, bentonite 10%, sawdust 6%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, MgO 2.10%.

[0045] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mix and sieve electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0046] Example 7 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 85%, bentonite 15%, sawdust 6%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, MgO 2.10%.

[0047] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mix and sieve electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0048] Comparative Example 2 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 80%, bentonite 20%, sawdust 6%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, MgO 2.10%.

[0049] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mix and sieve electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0050] Comparative Example 3 The mass percentages of the raw material components in this embodiment are: electrolytic manganese slag 95%, bentonite 5%, and sawdust 10%; water accounts for 30% of the total mass of the raw materials. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0051] The preparation process steps are as follows: Put the electrolytic manganese slag into an oven at 105℃ for drying, take out the electrolytic manganese slag, pour it into a crusher for crushing and pass through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mix and sieve electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 450°C, preheating time of 30 min, roasting temperature of 1050°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0052] Comparative Example 4 In this embodiment, the mass percentage of each component of the raw material is: electrolytic manganese slag 95%, bentonite 5%, and sawdust 6%; water accounts for 30% of the total mass of the raw materials, and the roasting temperature is 1030° C. The main components and mass contents of the electrolytic manganese slag are: SiO2 42.2%, Al2O3 13.09%, CaO 8.03%, Fe2O3 4.79%, MnO 3.02%, and MgO 2.10%.

[0053] The preparation process steps are as follows: a. Dry the electrolytic manganese slag in an oven at 105℃, take out the electrolytic manganese slag, pour it into a crusher, and crush it and pass it through a 60-mesh sieve; bentonite does not need to be sieved; sawdust is directly sieved through a 60-mesh sieve; b. By weight, manually mix and sieve electrolytic manganese slag, bentonite, sawdust and water to obtain a mixed raw material; c. Take 0.8g~1.4g of the mixture and granulate it manually. Put the raw material balls into an oven at 105℃ to dry them. After cooling, the molded ceramsite is obtained. d. Place the formed ceramsite in a muffle furnace and roast it under the conditions of preheating temperature of 400°C, preheating time of 30 min, roasting temperature of 1030°C, holding time of 10 min, and heating rate of 5°C / min. After autothermal cooling, the finished ceramsite is obtained with a particle size of 8mm~15mm.

[0054] The bulk density, apparent density, 1h water absorption rate and cylinder compressive strength of the electrolytic manganese slag sintered ceramsite prepared in Comparative Examples 1 to 4 were tested, and the reference standard was GB / T 17431.2 2010 "Light aggregate and its test method Part 2: Light aggregate test method", and the results are shown in Table 4.

[0055]

[0056] Comparing Comparative Example 1 with Example 6 and Example 7, it is obvious that after adding bentonite, the bulk density and cylinder pressure strength of ceramsite increase with the increase of bentonite dosage, and the 1h water absorption rate decreases therewith. Comparative Example 2 is compared with Example 6 and Example 7. When the amount of bentonite is increased to 20%, although the various properties of ceramsite meet the requirements, the dosage of electrolytic manganese slag is significantly reduced, and the cost is significantly increased, which is disadvantageous. Comparative Example 3 is compared with Example 6 and Example 7. When ceramsite is added with appropriate sawdust, the bulk density of ceramsite is reduced, and the 1h water absorption rate is increased, but when the dosage of sawdust is too much, the 1h water absorption rate of ceramsite will exceed 10%. Comparative Example 4 is compared with Example 6 and Example 7. Properly increasing the roasting temperature can greatly improve the cylinder pressure strength of ceramsite and reduce the 1h water absorption rate. However, the bulk density of ceramsite also increases therewith. If the roasting temperature is too low, it cannot meet the requirements. In summary, the scheme of the present invention can obtain high-strength ceramsite under the condition of high dosage of electrolytic manganese slag and without adding additional foaming agent and flux of higher purity. It is an economically feasible and environmentally friendly method for preparing high-strength ceramsite based on electrolytic manganese slag.

[0057] Application Example 1 The ceramsite prepared in Example 3 was used as lightweight aggregate to prepare lightweight aggregate concrete.

[0058] This application example designs three different types of ceramsite, namely electrolytic manganese slag sintered ceramsite, clay sintered ceramsite, and fly ash unfired ceramsite.

[0059] The raw material components in this embodiment are calculated by weight and include: 400 parts of cementitious material, 784 parts of electrolytic manganese slag sintered ceramsite, 639 parts of river sand, 160 parts of water, and 4 parts of carboxylic acid water reducer.

[0060] 400 parts of cementitious materials, 830 parts of sintered clay aggregate, 639 parts of river sand, 160 parts of water, and 4 parts of carboxylic acid water reducer.

[0061] 400 parts of cementitious materials, 748 parts of fly ash unburned ceramsite, 639 parts of river sand, 160 parts of water, and 4 parts of carboxylic acid water reducer.

[0062] The preparation process steps are as follows: a. Pre-absorb water for 1 hour and wipe off the surface moisture for later use; b. Accurately measure ceramsite, river sand and cementitious materials, pour them into the mixer and mix for about 5 minutes; c. Accurately measure water and water reducing agent, add them into the aggregate mixture and stir for about 3 minutes, and the electrolytic manganese slag ceramsite concrete mixture is ready; d. Use a cubic test mold to form the test piece, demould it and perform standard curing after 24 hours.

[0063]

[0064] Compared with other types of expanded clay on the market, electrolytic manganese slag expanded clay concrete has the highest compressive strength. The density of electrolytic manganese slag expanded clay concrete meets the requirements of 1800 density grade in the "Technical Standard for Application of Lightweight Aggregate Concrete" JGJ / T12-2019, and the 28d compressive strength meets the strength standard of LC30 concrete in the specification.

[0065] The above embodiments should be understood as being merely used to illustrate the present invention in more detail and specifically, and should not be understood as limiting the present invention in any form. Although some materials and operating methods used to implement the present invention are well known in the art, the present invention is still described as detailed as possible herein. In the context, unless otherwise specified, the materials and operating methods used in the present invention are well known in the art.

Claims

1. A method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite, characterized in that: The raw materials consisting of electrolytic manganese slag, bentonite and sawdust are dried, crushed and mixed, and then water is added to mix and granulate to obtain granules; the granules are dried, roasted and cooled to obtain the granules.

2. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1, characterized in that: The electrolytic manganese slag and the bentonite are composed of the following mass percentages: 80-95% electrolytic manganese slag and 5-20% bentonite; The mass of the sawdust is 4% to 8% of the total mass of the electrolytic manganese slag and the bentonite.

3. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1 or 2, characterized in that: The main components and mass contents of the electrolytic manganese slag are: SiO2 37.52-46.22%, Al2O3 10.09-15.06%, CaO 6.03-10.2%, Fe2O3 5.79-7.03%, MnO 2.54-3.61%, and MgO 1.82-2.68%.

4. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1 or 2, characterized in that: The raw materials are crushed to a particle size of 60-80 mesh.

5. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1, characterized in that: The mass ratio of the raw material to water is 100:25-30.

6. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1, characterized in that: The drying conditions are as follows: temperature of 100-105° C. and time of 4-5 h.

7. The method for preparing an environmentally friendly electrolytic manganese slag-based high-strength ceramsite according to claim 1, 2, 5 or 6, characterized in that: The calcination process is as follows: preheating at 350-550°C for 10-30min at a heating rate of 3-8°C / min, then heating to 1030-1070°C, and sintering for 5-20min.

8. An environmentally friendly electrolytic manganese slag-based high-strength ceramsite, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.